Nepal - Public Sector Accounting and Auditing : A Comparison to International Standards - World Bank (Washington, DC, 2012)
This assessment of public sector accounting and auditing in Nepal is intended to assist with the implementation of more effective public financial management (PFM) through better quality accounting and public audit processes. It is intended to provide greater stimulus for more cost- effective outcomes of government spending. The specific objectives are (a) to provide the country's accounting and audit authorities and other interested stakeholders with a common well- based knowledge as to where local practices stand in accordance with the internationally developed standards of financial reporting and audit; (b) to assess the prevailing variances; (c) to chart paths to reduce the variances; and (d) to provide a continuing basis for measuring improvements.